Bird collision with power lines: estimating carcass persistence and detection associated with ground search surveys. Issue 11 (27th November 2017) - Borner, L.; Duriez, O.; Besnard, A.; Robert, A.; Carrere, V.; Jiguet, F.
Abstract: The quantification of bird mortality due to collision with power lines is complicated by the heterogeneity of survey methods used and the bias related to searching for carcasses on the ground (e.g., carcass persistence and imperfect detection by observers). To estimate the bias associated with ground search surveys, we conducted three 30‐d trials to test carcass persistence by placing and monitoring carcasses of red‐legged partridges ( Alectoris rufa ) and common pheasants ( Phasianus colchicus ) below power lines at 14 sites. We also conducted two detection experiments, testing the ability of 19 observers to detect bird carcasses. We used survival analysis and generalized linear mixed‐effects models to investigate the effects of site, habitat, carcass size, and survey period on both carcass persistence and detection. We also investigated the effect of carcass age on carcass persistence and the effect of the observer on carcass detection. Our findings show significant variations in carcass persistence between sites and survey periods, as well as significant interaction between these variables. The daily carcass persistence probability was highly variable between sites, with an up to eightfold variation. Carcass detection increased with increasing carcass size and was significantly affected by the microhabitat surrounding the carcass; it also varied between observers. These findings suggest that both carcass persistence and detection vary strongly and unpredictably at a small scale. As a result, conservation managers should be encouraged to conduct carcass persistence and detection experiments on sites where they aim to produce unbiased estimates of bird mortality below power lines, and these trials should be carried out in conditions similar to the mortality survey. A large‐scale, unbiased, and accurate estimate of bird collision mortality due to power lines may require substantial field effort, with a survey frequency of more than once a week.